Recent Advances in Mechanism Design for Robotics Proceedings of the 3rd IFToMM Symposium on Mechanism Design for Robotics - Bai, Shaoping; Ceccarelli, Marco; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This volume contains the Proceedings of the 3rd IFToMM Symposium on Mechanism Design for Robotics, held in Aalborg, Denmark, 2-4 June, 2015. The book contains papers on recent advances in the design of mechanisms and their robotic applications. It treats the following topics: mechanism design, mechanics of robots, parallel manipulators, actuators and their control, linkage and industrial manipulators, innovative mechanisms/robots and their applications, among others. The book can be used by researchers and engineers in the relevant areas of mechanisms, machines and robotics.
Preface -- Linkage and Manipulators -- Finger mechanisms for robotic hands -- Dimensional Synthesis of One-Jointed Multi-Fingered Hands -- A Modular Shape-Adaptive Mechanism for Robust Robotic Grasping -- Mass equivalent dyads -- A Light Weight Arm Designed with Modular Joints -- Dynamic balancing conditions of planar parallel manipulators -- Design and Characterization of a New 5-DOF Arc Welding Robot Optimization of Grinding Parameters for Twist Drill in Biglide Parallel Machine -- Kinematics and Singularity Analysis of a 3-RRR Planar Hybrid Mechanism -- A Method to Estimate the Encoder Dependent Repeatability of General Serial Manipulators -- Innovative mechanism/robot and their applications -- Designing and Implementing an Interactive Social Robot from Off-the-shelf Components -- Portable Design and Range of Motion Control for an Ankle Rehabilitation Mechanism Capable of Adjusting to Changes in Joint Axis -- Dynamic Modeling and Torque Distribution of a Climbing Hexapod Robot -- Development and Simulation of an Automated Twistlock Handling Robot System -- Grinding Methodology Research for Helical Drill Based on the Biglide Parallel Grinder -- Actuators and Control -- Towards Safe Robotic Surgical Systems -- A Comprehensive Analytical Model and Experimental Validation of Z-shaped Electrothermal Microactuators -- Optimising Configurations of KUKA LWR4+ Manipulator for Calibration with Optical CMM -- Key Parameters Optimization of A Novel Tubular Double Excitation Windings Linear Switched Reluctance Motor -- Optimizing tracking performance of XY repositioning system with ILC -- Mechanism Design -- Shift Strategy for Railway Vehicle Transmissions -- Research and Analysis on transmission error of RV reducer used in robot -- Structural design and kinematic analysis of moving mechanism of insulator inspection robot -- Atlas Motion Platform Full-scale Prototype Design -- Simulation of Kinematic Pairs in the Calculation Mechanisms by Finite Element Method -- Mechanics of Robots -- Compliance Control and Design for Intelligent Lunar Robots -- Design Analysis and Dynamic Modeling of a High-speed 3T1R Pick-and-Place Parallel Robot -- Dynamic Characteristics of Two Cylinders$1 (BJoint Surfaces Based on Fractal Theory -- Modular system with varying contact elements for a reconfigurable parallel robot -- Study on Nonlinear Dynamics of RV Transmission System Used in Robot Joints -- Compliance Modeling and Error Compensation of a 3-Parallelogram Lightweight Robotic Arm -- A Design Method of Thin-Walled and Four-Point Contact Ball Bearings of Industrial Robots -- On the Elastostatics of Spherical Parallel Machines with Curved Links -- Accuracy Analysis of a Tripod Parallel Grinder -- General purpose software to solve the inverse dynamics and compute the internal efforts of non-redundant planar mechanisms -- Dynamic Modeling of Flexible Robot Manipulators - Acceleration-based Discrete Time Transfer Matrix Method -- Comparative study on the kinematic and static performance of two 1T2R parallel manipulators -- Parallel Manipulators -- Forward kinematic model of a new spherical parallel manipulator used as a master device -- Kinematics of a 6 DOFs manipulator with interchangeable translation and rotation motions -- Schoenflies Mode and Self-motions of a 2-RUU Parallel Manipulator -- Singularity Analysis of 2R1P Spherical Parallel Mechanisms -- Kinematics Analysis of 5-rod Car Suspension Mechanism with Singularities.s
Keywords: Engineering; Mechanics; Mechanics, Applied; Machinery; Robotics; Automation; Engineering; Machinery and Machine Elements; Robotics and Automation; Theoretical and Applied Mechanics; Electronic books